PENGARUH PERTUMBUHAN PENDUDUK, KESEMPATAN KERJA TERHADAP TINGKAT PENGANGGURAN TERBUKA DI PROVINSI JAWA TENGAH DENGAN ZIS SEBAGAI MODERASI - Triono, Triono; Nurhadi, Bayu (Ekonomi Syariah STAI Sangatta Kutai Timur, 2025)
This study aims to determine whether population growth and employment opportunities influence the open unemployment rate in Central Java during 2019–2023, with ZIS serving as a moderating variable. This study uses a quantitative approach with secondary data. The analytical technique applied is multiple regression using EViews 12 software. The sample in this study includes the entire population. The results show that population growth, employment opportunities, and ZIS simultaneously and significantly affect the open unemployment rate. Population growth has a negative and significant effect on the open unemployment rate, while employment opportunities have a positive and significant effect. Furthermore, ZIS is found to moderate the relationship between population growth, employment opportunities, and the open unemployment rate.